Perspectives croisées sur la coopération transatlantique Analyse à partir des politiques canadiennes et européennes - Angelet, Nicolas (European Studies, 2022)
This book gathers contributions by European and Canadian specialists in law, economics, international relations and political science and offers a rich overview of the many facets of Euro-Canadian relations.